Human immunodeficiency virus 1 envelope-initiated G2-phase programmed cell death. - Kolesnitchenko, V (1995)
Despite intensive investigation, no clearly defined mechanism explaining human immunodeficiency virus (HIV)-induced cell killing has emerged. HIV-1 infection is initiated through a high-affinity interaction between the HIV-1 external envelope glycoprotein (gp120) and the CD4 receptor on T cells. Cell killing is a later event intimately linked by in vitro genetic analyses with the fusogenic properties of the HIV envelope glycoprotein gp120 and transmembrane glycoprotein gp41. In this report, we describe aberrancies in cell cycle regulatory proteins initiated by cell-cell contact between T cells expressing HIV-1 envelope glycoproteins and other T cells expressing CD4 receptors. Cells rapidly accumulate cyclin B protein and tyrosine-hyperphosphorylated p34cdc2 (cdk1) kinase, indicative of cell cycle arrest at G2 phase. Moreover, these cells continue to synthesize cyclin B protein, enlarge and display an abnormal ballooned morphology, and disappear from the cultures in a pattern previously described for cytotoxicity induced by DNA synthesis (S phase) inhibitors. Similar changes are observed in peripheral blood mononuclear cells infected in vitro with pathogenic primary isolates of HIV-1.